The Importance of the Gradar Method in Job Analysis and Evaluation - Dalache, Dalila; Meddah, Lakhdar (Finance and Business Economies Review, 2022)
The study aims to define and determine the importance of the Gradar approach to job analysis and evaluation in light of the lack of transparency and flexibility of some traditional methods of job evaluation, and the development of new approaches in the context of technological development and the enlarging use of information networks in order to create a practical and understandable job and an existing system that integrates the current results of work sciences and organizational theory; The study concluded with a statement of the need to develop optimal efficiency models for the organization based on graded career paths, job families and grades, and to calculate the value of the work situation, with the objectif of developing jobs, and competencies and optimal performance.